Case report: Bitter vertigo - Goldschagg, Nicolina; Brem, Christian; Strupp, Michael (Frontiers in Neurology, 2022)
Background There are many causes of episodes of vertigo and very few causes of episodes of changes in taste, and the combination of the two is very rare. Here, we describe a patient with recurrent short episodes of vertigo in combination with simultaneous episodes of recurrent paroxysmal dysgeusia and altered feeling on the left side of face. The symptoms were caused by compression of the vestibulocochlear nerve and the facial nerve due to dolichoectasia of the basilar artery. Methods The patient was diagnosed in our routine clinical practice and underwent a complete neurological and neuro-otological examination, including video head impulse test, caloric irrigation, ocular and cervical vestibular evoked myogenic potentials, acoustic-evoked potentials, neuro-orthoptic examination, cranial MRI, and MR angiography. The patient was seen twice for follow-up. Case A 71-year-old patient primarily presented with a 2-year history of recurrent short episodes of spinning vertigo. Each of the episodes began with an altered feeling on the left side of the face, followed by a bitter taste on the left half of the tongue, and subsequently vertigo lasting for up to 15 s. The frequency of the attacks was high: up to 80 times per day. Laboratory tests revealed signs of a peripheral vestibular deficit on the left side. There were no signs of sensory or motor deficits or of altered taste between the episodes. An MRI of the brain showed an elongated basilar artery leading to an indentation of the facial and vestibulocochlear nerves on the left side. Conclusion We propose a neurovascular compression in the proximal part of two cranial nerves because of pulsatile compression by the elongated basilar artery with ephatic discharges as the cause of the recurrent episodes. Consistent with the theory of ephatic discharges, treatment with the sodium channel blocker lacosamide for over six months with a final dosage of 200 mg per day p.o. led to a significant reduction of the attack frequency and intensity. This treatment option with a sodium channel blocker should therefore not only be considered in vestibular paroxysmia but also in cases of paroxysmal dysgeusia.